2021
DOI: 10.1371/journal.pone.0259077
|View full text |Cite
|
Sign up to set email alerts
|

Global estimated Disability-Adjusted Life-Years (DALYs) of diarrheal diseases: A systematic analysis of data from 28 years of the global burden of disease study

Abstract: Background Diarrheal disease (DD)-associated mortality has declined since 1990; however, the incidence of DD has experienced a less-pronounced decrease. Thus, it is important to track progress in managing DD by following loss of healthy years. A disability-adjusted life-year (DALY), which combines data on years-of-life lost (YLL) and years-lived with-disability (YLD), is a metric that can track such a burden. Methods and findings Using all 28 years of data in the Global Burden of Diseases, Injuries, and Risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Diarrheal disease is still the most burdensome water and sanitation related disease worldwide (Prüss‐Ustün et al., 2019). Yet, an analysis of the recent global evidence has shown that the DALYs associated to diarrheal disease has decreased from 1990 to 2017 (Karambizi et al., 2021). This is congruent with these results showing a significant trend of increasing water and sanitation access as closely related with higher human development metrics across the 21st century.…”
Section: Discussionmentioning
confidence: 99%
“…Diarrheal disease is still the most burdensome water and sanitation related disease worldwide (Prüss‐Ustün et al., 2019). Yet, an analysis of the recent global evidence has shown that the DALYs associated to diarrheal disease has decreased from 1990 to 2017 (Karambizi et al., 2021). This is congruent with these results showing a significant trend of increasing water and sanitation access as closely related with higher human development metrics across the 21st century.…”
Section: Discussionmentioning
confidence: 99%
“…Predictive statistical modeling of 23 pathogens has been used to estimate the global total deaths associated with and attributable to antimicrobial resistance of bacteria in 2019 to be 4.95 million and 1.27 million, respectively, with E. coli being responsible for most of the deaths with those associated with and attributable to antimicrobial resistant E. coli at 23.4% and 24.3%, respectively ( Fernandez, 2022 ). Even without antimicrobial resistance, E. coli poses a significant health risk, as it is one of the major bacterial species contributing to diarrheal diseases and remains the second biggest killer of children below 5 years old after pneumonia, causing 0.437 million deaths annually ( International Vaccine Access Center, 2020 ; Karambizi et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Gut pathogenic bacteria that cause diarrhea diseases such as Shigella and Escherichia coli pose a great social and economic burden . In 2016, diarrhea diseases were responsible for 1.3 million deaths worldwide and were listed as the fifth leading cause of death in small children (age below 5 years) and eighth in all ages . Furthermore, the emergence of multidrug-resistant bacteria complicates the treatment of infection, and the limited availability of novel antimicrobial agents urges the need for alternative therapeutic options.…”
Section: Introductionmentioning
confidence: 99%